Re-visiting history, re-negotiating identity in two black British fictions of the 21st Century: Caryl Phillips’s A distant shore (2003) and Buchi Emecheta’s The new tribe (2000) - Moudouma Moudouma, Sydoine (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (English Literature))--University of Stellenbosch, 2009.